2018
DOI: 10.3389/fpubh.2018.00064
|View full text |Cite
|
Sign up to set email alerts
|

Parental Factors Influencing the Development of Early Childhood Caries in Developing Nations: A Systematic Review

Abstract: BackgroundEarly childhood caries (ECC) is one of the most prevalent and chronic conditions of childhood. Various factors including biological and dietary factors along with an overlay of parental social factors have been found to be associated with the progression of ECC. The objective of this systematic review is to synthesize available literature and to identify parent-level proximal and distal risk factors associated with the development of ECC in developing nations.MethodsStudies conducted in developing na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
5
17

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(103 citation statements)
references
References 40 publications
4
77
5
17
Order By: Relevance
“…Poor family SES negatively correlated with high quality and affordability of oral health services, and thus those children had restricted access to oral health services. Social support is a positive factor for oral health-related quality of life [21], which is consistent with the results of this study, indicating that children who lived in an environment where neighbors were willing to help with close-knit relationships, were less likely to be edentulous in This study identified an unexpected association between parents with high school education or above and edentulism, suggesting that having parents who had high education did not contribute to decrease the prevalence of edentulism, which is inconsistent with previous studies [51]. The age of respondents was 45+ years old, born between 1950s and 1970s, they went through their whole childhood and early adulthood before1978, when China was mainly an agricultural society and industrially undeveloped.…”
Section: Discussioncontrasting
confidence: 54%
“…Poor family SES negatively correlated with high quality and affordability of oral health services, and thus those children had restricted access to oral health services. Social support is a positive factor for oral health-related quality of life [21], which is consistent with the results of this study, indicating that children who lived in an environment where neighbors were willing to help with close-knit relationships, were less likely to be edentulous in This study identified an unexpected association between parents with high school education or above and edentulism, suggesting that having parents who had high education did not contribute to decrease the prevalence of edentulism, which is inconsistent with previous studies [51]. The age of respondents was 45+ years old, born between 1950s and 1970s, they went through their whole childhood and early adulthood before1978, when China was mainly an agricultural society and industrially undeveloped.…”
Section: Discussioncontrasting
confidence: 54%
“…Thus, we found a smaller proportion of children with caries compared with caries‐free children. The prevalence of dental caries worldwide ranges from 23% to 90% and is associated with a lower socio‐economic status …”
Section: Discussionmentioning
confidence: 99%
“…Parental factors such as education and income are signi cant risk factors in the developing of ECC [25]. Therefore, children from rural areas should be given more attention in order to reduce ECC.…”
Section: Discussionmentioning
confidence: 99%